Market integration and price transmission in the regional grain markets in Ethiopia - Dejene Gizaw Kidane (Journal of Applied Economics, 2022)
Persistent increases in basic food prices have become a critical challenge in Ethiopia since 2006. This paper assesses whether the structure of the grain market has contributed to the price increases. Traders having market power could create commodity price stickiness, implying that what goes up does not come down, leading to price increases. The study examines price linkages between principal grain markets in Ethiopia, using monthly prices from the wheat, maize, and teff markets. The Engle-Granger cointegration test is used to check for cointegration, while the Threshold Autoregressive Model is employed to investigate potential asymmetric price transmission. The findings indicate that major grain markets in Ethiopia are well integrated. Moreover, the threshold cointegration model reveals that they are characterized by symmetric adjustment. Hence, I argue that there is insufficient evidence to support the claim that market structure contributes to the price increase in Ethiopian grain markets.
Keywords: 330; Asymmetry; Ethiopia; price transmission; spatial grain prices; threshold cointegration